Perlindungan Hukum terhadap Konsumen yang Dirugikan atas Tidak Terteranya Informasi Kandungan Non Halal dalam Produk Makanan yang Diimport - Gede Mahesa Priyambada Kusuma; I Nyoman Putu Budiartha; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2022)
Most of the Indonesian people adhere to the Islamic religion which must get a sense of security regarding products/goods that do not contain content that is not allowed in their religion. This trust arises when the entrepreneur holds a halal certification which can be seen by the buyer on the packaging label after being registered. This study aims to analyze and describe the legal protection for consumers who are harmed by the absence of information on non-halal content in imported food products. This study uses a normative legal approach, the data comes from legal materials and literature. The results of the study indicate that one form of legal protection for the people of Indonesia is contained in Law no. 8 of 1999 concerning Consumer Protection which includes protection of goods and/or services. The form of responsibility of business actors to provide compensation is regulated in Articles 19 to 28 of the UUPK.